2021
DOI: 10.1109/access.2021.3076346
|View full text |Cite
|
Sign up to set email alerts
|

Monocular Depth Estimation Based on Multi-Scale Depth Map Fusion

Abstract: Monocular depth estimation is a basic task in machine vision. In recent years, the performance of monocular depth estimation has been greatly improved. However, most depth estimation networks are based on a very deep network to extract features that lead to a large amount of information lost. The loss of object information is particularly serious in the encoding and decoding process. This information loss leads to the estimated depth maps lacking object structure detail and have non-clear edges. Especially in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The multi-scale feature fusion is an effective method to deal with low-level feature loss. The Fuse Feature Pyramid (FFP) is a usual method to aggregate different scales feature, such as Chen et al [17], and Yang et al [18], but these models have a lot of parameters due to sampling the features too many times during building the FFP. To reduce the parameters, SU and ST are designed in this work.…”
Section: Su and Stmentioning
confidence: 99%
See 4 more Smart Citations
“…The multi-scale feature fusion is an effective method to deal with low-level feature loss. The Fuse Feature Pyramid (FFP) is a usual method to aggregate different scales feature, such as Chen et al [17], and Yang et al [18], but these models have a lot of parameters due to sampling the features too many times during building the FFP. To reduce the parameters, SU and ST are designed in this work.…”
Section: Su and Stmentioning
confidence: 99%
“…Based on this excellent work, Chen et al [17] proposed a Fused Feature Pyramid (FFP) and a residual pyramid to predict depth maps. Yang et al [18] built an FFP and used an ASFF (Adaptively Spatial Feature Fusion) structure [29] to fuse the different scale depth maps to keep the structure information. Although Chen et al [17] and Yang et al [18] showed a great performance, their model has a lot of parameters for building the FFP.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations